2013
DOI: 10.1002/pen.23699
|View full text |Cite
|
Sign up to set email alerts
|

Novel amphiphilic conetworks based on compatibilized NBR/SBR–montmorillonite nanovulcanizates as membranes for dehydrative pervaporation of water–butanol mixtures

Abstract: Nanocomposite vulcanizates comprising the poorly compatible acrylonitrile butadiene rubber/styrene butadiene rubber blend are homogenized with 20 parts per hundred montmorillonite forms showing various levels of amphiphathicity: slightly hydrophobic (Mont‐25/50) and highly hydrophobic (Mont75/100) as compared to the highly hydrophilic pristine form (Mont‐0). The purpose of the amphiphathicity is to afford simultaneous binding sites for the poorly compatible components. Thus maximum compatibility is reached wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…On the contrary, the diffusivity shows good correlation with the slope (a) values obtained from the relation V ro / V rf versus e − z (not shown), where it could be simply concluded that, the higher the strengthening action of a given montmorillonite form, the lower the diffusivity. We proved previously that this is basically dictated by the acquired free volume of the resulting interpenetrating co‐networks, which is a function of the extent of organophilization for each inserted clay form.…”
Section: Resultsmentioning
confidence: 74%
“…On the contrary, the diffusivity shows good correlation with the slope (a) values obtained from the relation V ro / V rf versus e − z (not shown), where it could be simply concluded that, the higher the strengthening action of a given montmorillonite form, the lower the diffusivity. We proved previously that this is basically dictated by the acquired free volume of the resulting interpenetrating co‐networks, which is a function of the extent of organophilization for each inserted clay form.…”
Section: Resultsmentioning
confidence: 74%
“…Moreover, it has no harmful effects on the microorganism . The use of hydrophobic membranes such as styrene butadiene rubber (SBR), ethylene propylene diene rubber (EPDM), polytetrafluoroethylene (PTFE), polypropylene (PP), polyurethane (polyether based) (PUR), polyether block‐amide (PEBA), poly(vinylidinedifluoride) (PVDF), poly(methoxy siloxane) (PMS), polydimethylsiloxane (PDMS), poly(1‐(trimethylsilyl)‐1‐propyne) (PTMSP) and polyamide‐imide (PAI) containing cyclodextrin (CD) has been reported in the literature for butanol separation through the process of pervaporation …”
Section: Introductionmentioning
confidence: 99%
“…the effects of the same nanofiller concentration on PS/PB blend thin film stability was studied (94). Few papers deal with elastomer-elastomer nanocomposites (95,96).…”
Section: Thermoplastic-elastomer Polymer Blend Nanocompositesmentioning
confidence: 99%